PV/Fuel Cell/ Superconducting Magnetic Energy Storage Coupled with VSG to Improve Frequency and Voltage Regulation of Power Grid - Alsharif, Alhassan; Khalid, Muhammad (2023 IEEE PES GTD International Conference and Exposition (GTD), 2023)
The growing types of renewable energy resources that connect to the power grid are being increased globally to reduce the accelerating impact of climate change. Even with various types of resources, they are resembled as inverter-based machines. The inverters are new elements introduced to the power grid in huge bulk. The integration of large number of inverter-based renewable energy resources change the dynamical behavior of the existing grid due to lacking rotating mass and damping characteristics. The inertia and the damping play crucial role into expanding the penetration of the renewable energy but grid-following converters do not solve the problem. Therefore, multiple research works targeted the behavior of the synchronous machine to be copied into the inverter through different control approaches. The inverter becomes of grid-forming nature and called Virtual Synchronous Generator (VSG), which this paper presents. A MATLAB simulation of PV, Fuel Cell and SMES coupled with PSO enhanced VSG are grid-connected to regulate the frequency and voltage and prompt stability.